Stemness-Associated Markers Are Expressed in Extracranial Arteriovenous Malformation - Luke Krishnan, Claire S.; Brasch, Helen D.; Patel, Josie; Bockett, Nicholas; Paterson, Erin; Davis, Paul F.; Tan, Swee T. (Frontiers in Surgery, 2021)
Objectives Arterio-venous malformation (AVM) consists of a nidus with poorly formed low-resistance vessels in place of a functional capillary network. The role of somatic mutations in embryonic stem cells (ESCs) and vascular anomalies, and the presence of primitive populations in vascular anomalies, led us to investigate the presence of a primitive population in extracranial AVM. Methods Extracranial AVM tissue samples from 12 patients were stained for stemness-associated markers OCT4, SOX2, NANOG, KLF4 and c-MYC using immunohistochemical staining. In situ hybridization (ISH) was performed on six tissue samples to determine transcript expression. Western blotting and RT-qPCR were performed on two AVM-derived primary cell lines to determine protein and transcript expression of these markers, respectively. Immunofluorescence staining was performed on two tissue samples to investigate marker co-localization. Results Immunohistochemical staining demonstrated expression of OCT4, SOX2, KLF4 and c-MYC on the endothelium and media of lesional vessels and cells within the stroma of the nidus in all 12 AVM tissue samples. ISH and RT-qPCR confirmed transcript expression of all five markers. Western blotting showed protein expression of all markers except NANOG. Immunofluorescence staining demonstrated an OCT4+/SOX2+/KLF4+/c-MYC+ population within the endothelium and media of the lesional vessels and cells within the stroma of the AVM nidus. Conclusions Our findings may suggest the presence of a primitive population within the AVM nidus. Further investigation may lead to novel therapeutic targeting of this population.